Anton Chekhov through the eyes of Russian thinkers: Vasilii Rozanov, Dmitrii Merezhkovskii and Lev Shestov - Ure, Adam; Tabachnikova, Olga (Anthem Press, 2010)
This volume offers modern perspectives, from a strong international team of scholars, on the perception of Anton Chekhov's works by three leading cultural figures of the Silver Age of Russian culture - Vasilii Rozanov, Dmitrii Merezhkovskii and Lev Shestov
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Shestov, Lev -- 1866-1938 -- Criticism and interpretation; Rozanov, V. V -- (Vasiliĭ Vasilʹevich) -- 1856-1919 -- Criticism and interpretation; Merezhkovsky, Dmitry Sergeyevich -- 1865-1941 -- Criticism and interpretation; Chekhov, Anton Pavlovich -- 1860-1904 -- Criticism and interpretation